Fluid structure interaction simulation of large deformation and added-mass effect using OpenFOAM - Zakaria, Mohamad Shukri; Abdullah, Haslina; Ahmad, Kamarul Arifin (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2018)
Large deformation and added mass effect (i.e., closed density between vessel and blood) dominate the Fluid Structure Interaction (FSI) simulation instability on the numerical algorithm. Therefore, in this article, we provide numerical study of such problem using FSI partition coupling approach. The FSI solver were develop using CFD Open source solver library OpenFOAM, in which Arbitrary Lagrangian Eulerian (ALE) Finite Volume Method (FVM) solver for fluid with automatic mesh motion and updated lagrangian FVM solver is used for elastic solid. The robustness of the solver as well as its accuracy is compared to the monolithic solution of classical FSI benchmark test case of flapping flag attaches on the back of cylinder. Finally, implications of the results and future research directions on efficient FSI simulation especially in heart valve applications are also presented.